Interaction of visually impaired students in mainstream class a case study - Estoque, Nova B.
Education is everyone's right. However, there are less fortunate people who are unable to acquire formal education, such as handicapped people. But with the help of some institutions handicapped people are able to study. These institutions provide the necessary trainings and things needed in the studies of the handicapped students. This study entitled ?Interaction of Visually Impaired Students in Mainstream Class: A Case Study? was accordingly conducted to determine the experiences of visually impaired students in mainstream class, how they cope with different situations in the school or classroom and to describe how they relate to sighted students and teachers. The study chooses five respondents to represent the visually impaired students as permitted by the principal of Davao School and Rehabilitation Center for the Visually Impaired, and eight selected sighted students, assigned as dictators (those who assist the visually impaired during dictation), to present the regular students. Advisers were also interviewed and the principals of the schools. This was conducted in two different schools in Davao City, the Davao School and Rehabilitation Center for Visually Impaired and Talomo National High School. A finding of the study revealed that integration program of the visually impaired students in the mainstream class is not successful. Visually impaired students have found difficulty studying in mainstream class. In most of the lessons they have to rely for the help of their dictators and not all times their dictators are there to help them. Moreover, visually impaired students cannot participate in many classroom activities because the teachers just give them considerations. And so, the visually impaired students do not attain full learning in the areas of science and mathematics. Furthermore, if the visually impaired students found difficulty in the mainstream class, the sighted students, particularly , the dictators also found difficulty having them in the mainstream class. Though, the dictators pity the visually impaired classmates, they can not avoid become annoyed with them during dictation times because it is a burden on their part. The dictators cannot concentrate doing the task for themselves. Moreover, the teachers also found difficulty handling the visually impaired students since there was no special training given to them on the right methods for teaching the visually impaired students. This effects the learning of the visually impaired students as well as their effectiveness as teachers.
Thesis, Undergraduate (BA Social Science) -- U. P. in Mindanao